International transfer of technology under the TRIPS Agreement - Alhelali, Shaikhah (2017)
The international transfer of technology plays a critical role to developing countries. It enhances the economic development and welfare, in addition to reducing the gaps between developing and developed countries. The promotion of the international transfer of technology increases the capabilities of developing countries and assists them to gain more independency. Therefore, the central question that this thesis tries to answer is related to whether the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement) fosters international transfer of technology to developing countries or not. Developing countries as per the TRIPS Agreement are requested to comply with minimum standards of intellectual property (IP) protection, since they are linked to international trade under the World Trade Organisation (WTO) regime. So, in order to have balanced rights and obligations, we have to evaluate whether the TRIPS Agreement is benefiting all parties and whether the transfer of technology is well-managed under the TRIPS Agreement. The terms and conditions of the TRIPS Agreement will be analysed using the doctrinal legal method. We find that the TRIPS provisions are still far from fostering the international transfer of technology to developing countries although the preamble and its principles and objectives under Articles 7 and 8 emphasize its importance. In addition to analysing the provisions related to transfer of technology under the United Nation Framework Convention on Climate Change (UNFCCC) through both the doctrinal legal method and empirical study on the transfer of environmental sound technologies under the Clean Development Mechanism (CDM) that was established in Kyoto Protocol adopted in 1997. We find that CDM works mainly for reducing the greenhouse gases (GHG) while the international transfer of technology is not an obligatory element of it. We reached a number of recommendation to improve the current situation and enhance more development in the field of international transfer of technology. At the beginning we need to define the international transfer of technology in the TRIPS Agreement. Lack of definition results in challenges and obstacles in the way we are evaluating its promotion. In addition, TRIPS Agreement is required to create a new mechanism, similar to the CDM, but particularly for the promotion of international transfer of technology.